The Effectiveness of the Multiple Intelligences Approach in Remedial Calistung Instruction in Elementary Schools: A Systematic Literature Review-Based Analysis - Katriana, Yuli; Siswanto, M Bambang Edi; Mariana, Neni (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to systematically evaluate the effectiveness of the Multiple Intelligences (MI) approach for remedial foundational reading, writing, and arithmetic (calistung) instruction in elementary schools Methodology: A Systematic Literature Review (SLR) was conducted according to the PRISMA framework. A comprehensive search of literature published between 2020-2025 was performed across multiple academic databases using predefined keywords. A total of 20 relevant studies were identified, critically appraised, and thematically synthesized. Main Findings: The MI approach shows positive potential in improving calistung skills, particularly when integrated with active strategies like Problem-Based Learning and using MI-based worksheets. However, most existing studies have key methodological limitations, including small sample sizes, weak designs, and a lack of longitudinal data. Effectiveness is highly dependent on implementation quality and context. Novelty/Originality of this study: This review provides a novel, focused synthesis of recent empirical evidence on MI for remedial calistung, a specific and critical educational context. It advances knowledge by identifying a consistent research-practice gap and offering concrete, evidence-based recommendations for future research and curriculum integration, moving beyond general theoretical discussion.